Evaluation of a livestock financing project in Bangladesh: Navigating operational, environmental, and behavioral challenges - Ambler, Kate; Bakhtiar, M. Mehrab; de Brauw, Alan; Uddin, Mohammad Riad (International Food Policy Research Institute, 2023)
Smallholder farmers in low- and middle-income countries have limited access to finance, due to the pau city of banks and other financial institutions in rural areas. As a result, banks and other formal financial institutions tend not to know much about farming as a business, and therefore they hesitate to extend credit to farmers. Such reluctance is often attributed to the elevated costs and risks linked with small, geographically dispersed farms, as well as the farmers' lack of collateral. Microfinance has emerged as a crucial intervention in bridging this gap. However, the fixed and rigid repayment structures of microfinance institutions (MFIs) often clash with the seasonal nature of agricultural production. This mismatch creates financial strain for farmers, who must manage cash flows that are inherently unpredictable due to factors like weather variability and market fluctuations. These challenges underscore the need for more flexible and tailored financial solutions.